Oral health and dental status in people with epilepsy in rural China. (February 2019) - Wang, Mengjie; Ding, Ding; Zhang, Qing; Zhu, Guoxing; Ge, Yan; Yang, Bin; Wang, Taiping; Kwan, Patrick; Wang, Wenzhi; Hong, Zhen; Sander, Josemir W.
Highlights: People with epilepsy have poor oral health and could easily get dental injury. Seizure frequency was associated with bad oral health habit and dental injury. Control of seizures should take precedence in epilepsy. More attention should be paid to oral health of people with epilepsy. Abstract: Purpose: We evaluated the oral health and dental status of people with epilepsy, and their relationship to seizure frequency, in a community cohort in rural China. Methods: A cross-sectional study of people with epilepsy was carried out in areas in Henan, Shanxi and Ningxia provinces of China. All participants underwent a specially designed "Oral health and Dental status Questionnaire". Univariate and multivariate analyses were used to explore the relationships between seizure frequency and oral health and dental status. Results: A total of 875 people participated. Almost two thirds (65.8%) reported brushing their teeth at least once a day but 634 (73.0%) brushed their teeth for less than 3 min each time. Only 80 (9.1%) had visited a dental clinic in the previous year. Multivariate logistic regression analysis showed that having 1–4 seizures/month (OR 0.60, 95%CI 0.40-0.90) or >4 seizures/month (OR 0.38, 95%CI 0.22-0.66) was associated with decreased odds of brushing teeth at least once a day, and higher seizure frequency was associated with increased odds of dental injury due to seizures (OR 2.07, 95%CI 1.22–3.50 for <1 seizure/month; OR 2.12, 95%CI 1.25–3.58 for 1–4 seizures/month; OR 3.09, 95%CI 1.57–6.07 for >4 seizures/month). Conclusion: Seizure frequency was significantly associated with seizure-related dental injury, and with the lack of good oral health practice. Improvement in the oral health of people with epilepsy in resource-poor areas should be encouraged.